2010
DOI: 10.1007/s00253-010-2771-4
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant artificial forisomes provide ample quantities of smart biomaterials for use in technical devices

Abstract: Forisomes are mechanoproteins that undergo ATP-independent contraction-expansion cycles triggered by divalent cations, pH changes, and electrical stimuli. Although native forisomes from Medicago truncatula comprise a number of subunits encoded by separate genes, here we show that at least two of those subunits (MtSEO1 and MtSEO4) can assemble into homomeric forisome bodies that are functionally similar to their native, multimeric counterparts. We expressed these subunits in plants and yeast, resulting in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 38 publications
1
76
0
Order By: Relevance
“…We recently reported that two M. truncatula SEO proteins (MtSEO-F1 and MtSEO-F4) assemble into spindle-like structures similar to native forisomes (Fig. 3A) when coexpressed as tagged and untagged versions in N. benthamiana (25,27), demonstrating the validity of this approach for the analysis of NtSEO assembly.…”
Section: Transient Coexpression In a Heterologous Background Providesmentioning
confidence: 69%
See 2 more Smart Citations
“…We recently reported that two M. truncatula SEO proteins (MtSEO-F1 and MtSEO-F4) assemble into spindle-like structures similar to native forisomes (Fig. 3A) when coexpressed as tagged and untagged versions in N. benthamiana (25,27), demonstrating the validity of this approach for the analysis of NtSEO assembly.…”
Section: Transient Coexpression In a Heterologous Background Providesmentioning
confidence: 69%
“…All fusion constructs were assembled in the pBShrGFP vector series containing the hrGFP (65) coding sequence fused to the CaMV 35S terminator. Fusions were obtained for NtSEO1, NtSEO2, and, as a control, forisome subunitencoding MtSEO-F1 (24,27). The detailed cloning procedure is given in SI Materials and Methods.…”
Section: Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Forisome smart materials are known to be capable of self assembly consisting of fibers of nanometer range. 46 Self assembly of forisome smart materials in heterologous background of N. benthamiana results in transient expression in epidermal cells. 35 It is therefore remarkable that forisomes can assemble in heterologous background.…”
Section: Role Of Electropotential Waves (Epws) In Forisomes Signalingmentioning
confidence: 99%
“…36.,37 Through the studies of Knoblauch it became evident that occlusion of sieve tube pores by crystalloid P-proteins is rapidly reversible and controlled by the Ca 2+ ñux. 46,47 On the basis of dynamic structural changes which are unique to the crystalline P-proteins of legumes distinguishes them from the non-dispersive phloem-specific protein bodies of other families (such as Urticaceae and Rosaceae). 48 Classically the phloem protein bodies have been classified namely into 2 broad categories.…”
mentioning
confidence: 99%